1977
DOI: 10.1056/nejm197710062971404
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Premature Beats and Mortality after Myocardial Infarction

Abstract: To assess the role of ventricular premature beats in influencing mortality of coronary patients, 1739 men with prior myocardial infarction were monitored for ectopic activity for one hour at a standard base-line examination, and followed for mortality for periods up to four years (average, 24.4 months). Analyses of survival taking into account other important prognostic variables establish that the presence of complex premature beats (R on T, runs of 2 or more, multiform or bigeminal premature beats) in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
2
12

Year Published

1979
1979
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 623 publications
(109 citation statements)
references
References 28 publications
3
92
2
12
Order By: Relevance
“…80 e Moss e cols. 87 concluíram que as arritmias ventriculares e a disfunção ventricular eram fatores de risco que se somavam à morte após infarto do miocárdio.…”
Section: Diretriz Da Sociedade Brasileira De Cardiologia Sobre Traunclassified
See 2 more Smart Citations
“…80 e Moss e cols. 87 concluíram que as arritmias ventriculares e a disfunção ventricular eram fatores de risco que se somavam à morte após infarto do miocárdio.…”
Section: Diretriz Da Sociedade Brasileira De Cardiologia Sobre Traunclassified
“…A separação e a perda de orientação das fibras miocárdicas taquicardia ventricular e a fibrilação ventricular 77 . A presença de arritmias ventriculares complexas, detectadas pelo Holter após a fase aguda do infarto do miocárdio, é indicativa de mau prognóstico para a evolução em médio prazo [78][79][80][81][82][83][84][85][86][87][88] .…”
Section: -Confirmação Diagnóstica Avaliação E Acompanhamento Prognósunclassified
See 1 more Smart Citation
“…An observational study demonstrated that premature ventricular complexes (PVCs) after a myocardial infarction increase the risk of sudden death [23]. As a result of this such patients were frequently treated with antiarrythmic drugs because they suppressed PVCs [24].…”
Section: Hierarchies Of Research Evidencementioning
confidence: 99%
“…Furthermore, as recently reviewed by Winkle (1980), certain types of ventricular arrhythmias detected by ambulatory electrocardiography (Holter monitoring) have been found to be a prognostic factor per se (Moss et al, 1979;Ruberman et al, 1977;Rehnqvist, 1978). It was decided to compare the reliability of the easy and inexpensive standard ECG with that of the time consuming and expensive' long-term electrocardiographic monitoring in the detection of ventricular arrhythmias in a population prone to sudden death.…”
Section: Introductionmentioning
confidence: 99%